(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
The Matrix converter technology draws significant interest in motor drive applications. This is due to the advantages it can offer, like providing high quality input and output currents and compact structure. However, some unsolved problems strict its industrial use, one of these main problems is the stability of operation caused by the voltage distortion and/or the load torque disturbances. Using steady state small signal analysis, the matrix converter drive system driving an induction motor and equipped with an input filter will be presented in this paper, the stability of the system will be examined and the factors that influence it will be defined. A method of investigating the complex system with multiple-inputs multiple-outputs in simple fashion will be presented. Matlab/Simulink computer software is used to obtain simulation results to verify the mathematical model. The analysis will be carried out using transfer function analysis and the migration of eigenvalues on the simulation results. Where it has noticed that the stability is significantly affected by the system parameters, while the damping resistor of the filter affect the system stability directly.